High-resolution topography of the Antarctic Peninsula combining TanDEM-X DEM and REMA mosaic - Dong, Yuting; Zhao, Ji; Floricioiu, Dana; Krieger, Lukas; Fritz, Thomas; Eineder, Michael (2020)
The Antarctic Peninsula (AP) is one of the widely studied polar regions because of its high sensitivity to climate change and potential contribution to global sea level rise. Precise DEMs at high spatial resolution are highly demanded for investigating the complex glacier system of the AP at fine scale. However, the two most recent high-resolution DEMs covering the AP area, the 12-m TanDEM-X DEM (TDM DEM) from bistatic InSAR data acquired between 2013 and 2014 and the Reference Elevation Model of Antarctica mosaic (REMA mosaic) at 8 m posting derived from optical data acquired between 2009 and 2017 have specific individual limitations. The TDM DEM has the advantage of good data consistency and few data voids, but there exist residual height errors in the non-edited DEM version. The REMA mosaic on AP has high absolute vertical accuracy (about 1 m) but suffers from large areas with data voids and a larger time span within the images used to generate DEM. To generate a consistent, gapless and high-resolution (12 m) topography product of the AP, we combine the TDM DEM and REMA mosaic by detecting and correcting the height errors in TDM DEM through a novel path propagation algorithm and multi-scale height error correction method based on the accurately calibrated REMA mosaic data. The resulting DEM was evaluated with laser altimetry data and the Root Mean Square Error (RMSE) of the resulting DEM has been reduced by about 50 % compared to the original TDM DEM. Remaining height errors especially due to phase unwrapping errors were successfully eliminated. The generated high-resolution DEM depicts the up-to-date topography of AP in detail and can be widely applied for glaciological studies at individual glaciers or at regional scale.